2015
DOI: 10.1111/ajt.13055
|View full text |Cite
|
Sign up to set email alerts
|

National Decline in Donor Heart Utilization With Regional Variability: 1995-2010

Abstract: The severe shortage of donor hearts limits the availability of transplantation for the growing population of patients with end-stage heart disease. We examined national trends in donor heart acceptance for transplant. OPTN data were analyzed for all potential adult cardiac organ donors between 1995 and 2010. Donor heart disposition was categorized as transplanted, declined for transplant or other. We studied changes in the probability of donor heart acceptance according to demographic and clinical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 18 publications
3
99
0
1
Order By: Relevance
“…Since initial suggestions that "male cardiac donors should probably be under the age of 35 and female donors under 40 years" (1), a wealth of studies, mainly based on single-center cohorts and national registry data, have been published that have challenged prior assumptions about donor heart selection. Current guidelines for heart selection, however, remain very broad and do not address many issues encountered in routine donor selection (2), thus creating highly variable selection patterns among centers (3). Donor selection remains a challenging and multifactorial decision that is influenced by imperfect donor information (and lack of data on how to interpret this information), a potential candidate's medical urgency, donor-recipient match considerations, and institutional risk tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Since initial suggestions that "male cardiac donors should probably be under the age of 35 and female donors under 40 years" (1), a wealth of studies, mainly based on single-center cohorts and national registry data, have been published that have challenged prior assumptions about donor heart selection. Current guidelines for heart selection, however, remain very broad and do not address many issues encountered in routine donor selection (2), thus creating highly variable selection patterns among centers (3). Donor selection remains a challenging and multifactorial decision that is influenced by imperfect donor information (and lack of data on how to interpret this information), a potential candidate's medical urgency, donor-recipient match considerations, and institutional risk tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to global organ shortage and groundbreaking developments in mechanical circulatory support, the number of heart transplantations declined and the number of implanted left ventricular assist devices (LVAD) markedly increased over the last decade [3][4][5]. Since 2010, 100% of patients in need for destination therapy, registered in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS), received continuous-flow (CF) pumps.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of more powerful imaging techniques such as real time 3D echocardiography and cardiac magnetic resonance imaging organ screening should become more efficient if these techniques are used in a systematic fashion. In a recent retrospective analysis of the United Network of Organ Sharing database Khush et al [1] showed that the percentage of donor hearts accepted for transplant decreased from 44% in 1995 to 29% in 2006 with an increase to 32% in 2010. Though increase in rejection rate of donor hearts has been based on age and co morbidities there are no evidence based guidelines to support this.…”
Section: Introductionmentioning
confidence: 99%
“…Though increase in rejection rate of donor hearts has been based on age and co morbidities there are no evidence based guidelines to support this. Hence efforts in this direction would be helpful [1] . In another retrospective investigation only two statistically relevant causes such as death and history of diabetes have been implicated in prolonged postoperative hospital stay and increased mortality respectively [2] .…”
Section: Introductionmentioning
confidence: 99%